PERAN GURU KRISTEN DALAM MENUNTUN SISWA MEMANDANG MATEMATIKA [THE ROLE OF CHRISTIAN TEACHERS IN GUIDING STUDENTS TO VIEW MATHEMATICS] - Dirgantoro, Kurnia Putri Sepdikasari; Soesanto, Robert Harry (Universitas Pelita Harapan, 2021)
Mathematics is a subject that is considered a scourge by most students. They think that mathematics is difficult, complicated, and boring. However, if we look at the process of creation, everything in this universe (including mathematics) is God's creation and everything is really good. This truth needs to be revealed to students by the mathematics teacher. Unfortunately, many math teachers make students dislike mathematics. Therefore, this paper aims to describe the role of Christian mathematics teachers to guide students in viewing mathematics according to God's perspective. The research method used is the literature study method. The results of this study indicate that the role of Christian mathematics teachers includes: (1) appreciating and exploring mathematics first; (2) developing the four teacher competencies; and (3) understand the objectives of learning mathematics. Christian mathematics teachers also need to be careful not to fall into the sin of idolatry and pride by asking the Holy Spirit for help to be enabled in each of their ministries.BAHASA INDONESIA ABSTRACT: Matematika merupakan salah satu mata pelajaran yang dianggap momok oleh siswa. Siswa menganggap bahwa matematika itu sulit, rumit, dan membosankan. Namun jika melihat pada proses penciptaan maka segala yang ada di alam semesta ini (termasuk matematika) merupakan ciptaan Allah dan semuanya sungguh amat baik. Kebenaran ini perlu disingkapkan kepada siswa oleh guru matematika. Namun, banyak guru matematika yang justru membuat siswa tidak menyukai matematika. Oleh sebab itu, tulisan ini bertujuan untuk memaparkan peran guru matematika Kristen di dalam menuntun siswa dalam memandang matematika sesuai dengan cara pandang Allah. Adapun metode penelitian yang digunakan adalah metode studi kepustakaan. Hasil penelitian ini memaparkan bahwa peran guru matematika Kristen meliputi: (1) mengapresiasi dan menjelajahi matematika terlebih dahulu; (2) mengembangkan keempat kompetensi guru; serta (3) memahami tujuan pembelajaran matematika. Guru matematika Kristen juga perlu berhati-hati agar tidak jatuh ke dalam dosa penyembahan berhala dan kesombongan dengan meminta pertolongan kepada Roh Kudus agar dimampukan dalam setiap pelayanannya.